Antinociceptive and Anti-Inflammatory Activities of Acetonic Extract from Bougainvillea x buttiana (var. Rose) - Gabriela Castañeda-Corral; Mayra Cedillo-Cortezano; Magdalena Aviles-Flores; Misael López-Castillo; Juan José Acevedo-Fernández; Vera L. Petricevich (MDPI AG, 2024)
Background:Bougainvillea x buttiana is an ornamental plant with antioxidant, anti-inflammatory, and cytotoxic activities, which has been traditionally used to treat respiratory diseases. This study aimed to investigate whether the acetonic extract of Bougainvillea x buttiana var. Rose (BxbRAE-100%) has analgesic and anti-inflammatory properties and its potential action mechanisms. Methods: Analgesic and anti-inflammatory activities were evaluated using three murine pain models and two acute inflammation models. In vitro, the ability of the extract to inhibit proteolytic activity and the activities of the enzymes phospholipase A2 (PLA2) and cyclooxygenase (COX) were evaluated. In silico analysis was performed to predict the physicochemical and Absorption, distribution, metabolism, and excretion (ADME) profiles of the compounds previously identified in BxbRAE-100%. Results: In vivo BxbRAE-100% decreased the nociceptive behaviors in the writhing model, the tail immersion, and the formalin test, suggesting that the extract has the potential to relieve pain at peripheral and central levels. Additionally, topical or oral BxbRAE-100% treatment reduced dose-dependent 12-O-Tetradecanoylphorbol-13-acetate (TPA)-induced ear inflammation and carrageenan-induced paw edema, respectively. In vitro, BxbRAE-100% significantly inhibited proteolytic activity and PLA2, COX-1 and COX-2 activities. In silico, the compounds previously identified in BxbRAE-100% met Lipinski's rule of five and showed adequate ADME properties. Conclusions: These results support the use of B. x buttiana in Traditional Mexican Medicine and highlight its potential for the development of new treatments for pain and inflammation.